Macroline, akuammiline, sarpagine, and ajmaline alkaloids from Alstonia macrophylla - Kam, Toh Seok; Lim, S.H.; Low, Y.Y.; Sinniah, S.K.; Yong, K.T.; Sim, K.S. (Elsevier, 2013)
A total of seventeen alkaloids, comprising six macroline (including alstofolinine A, a macroline indole incorporating a butyrolactone ring-E), two ajmaline, one sarpagine, and eight akuammiline alkaloids, were isolated from the stem-bark and leaf extracts of the Malayan Alstonia macrophylla. The structure and relative configurations of these alkaloids were established using NMR, MS and in several instances, confirmed by X-ray diffraction analysis. Six of these alkaloids were effective in reversing multidrug-resistance(MDR) in vincristine-resistant KB cells.